FSH/AMH Ratio and Adipocyte Size are Linked to Ovarian Dysfunction. (2nd July 2020) - Roberts, Jackson A.; Carpenter, Ryann M.; Blythe, Sarah N.; Toporikova, Natalia
ABSTRACT: Background and Aim: While the relationship between obesity and reproductive dysfunction is well known, the physiological mechanism behind obesity-related infertility remains unclear. Previous work suggests that follicle development prior to ovulation is disrupted in obese individuals. Follicle-stimulating hormone (FSH) and anti-Mullerian hormone (AMH) are two key regulators of follicle development, and the poorest reproductive outcomes have been recorded when these hormones are imbalanced. In order to understand how obesity impacts the reproductive axis, the present study induces reproductive dysfunction in female rats using a high-fat, high-sugar diet (HFHS). Results: In our study, several animals on the HFHS diet displayed abnormal estrous cycles. The HFHS diet also resulted in an increased prevalence of ovarian cysts and decreased formation of corpora lutea. Across all groups, the FSH/AMH ratio displayed a strong negative correlation with pre-antral, antral, and total follicle counts. Moreover, rats on the HFHS diet displayed larger adipocytes and produced higher levels of leptin than controls. When combined with average adipocyte size in multiple regression, the FSH/AMH ratio was strongly associated with cyst formation in the ovary. Conclusions: These findings provide strong evidence for the potential relevance of a combined FSH/AMH ratio as a marker of ovarian health and follicular status. Therefore, this ratio reflects a complex interaction between the reproductive and metabolic systems.